Faktor-Faktor yang mempengaruhi Kepuasan Konsumen dan Kaitannya Dengan Kesetiaan Merek pada Produk Kesehatan K-Link di Kota Banda Aceh - Rizal, Syamsul (Lembaga KITA, 2019)
The purpose of this study was to determine the factors of consumer satisfaction and how much influence on brand loyalty in K-link health food products in the city of Banda Aceh. The object of research is about the satisfaction and loyalty of consumer brands in K-Link health food products in Banda Aceh City with a total sample of 250 respondents. The results of this study indicate that there is a significant correlation (correlation coefficient) between the variables of customer satisfaction factors that include product attributes, service attributes and purchase attributes to brand loyalty that is equal to 0.649 or 64.9%. The results also showed that the three variables of consumer satisfaction had a strong influence on brand loyalty of K-link health food products that was 0.422 or 42.2%. The product attribute variable has a dominant influence on influencing consumer brand loyalty on K-Link health food products because this variable has a higher regression coefficient than the other two independent variables.Â Keywords: Consumer Satisfaction, Loyalty, Brand, K-Link Health Products.